Meningkatkan Kinerja Pemasaran melalui Orientasi Pasar dan Orientasi Kewirausahaan - Rizki Aulia; Miguna Astuti; Hariyanto Ridwan (JURNAL ILMIAH MANAJEMEN & BISNIS, 2019)
This study analyzes the influence of  market orientation and entrepreneurial orientation on performance  marketing on culinary small and medium enterpreses (SMEs) in Ciganjur region, South Jakarta. The  purpose of  this research  was carried   out to: (1) determine  the influence  of market  orientation  on performance  marketing; (2) determine the influence  of  entrepreneurial   orientation  effect  on performance  marketing. With descriptive quantitative approach, the sampling  techniques used in this research is total population sampling. The primary data are obtained through questionnaires to the 44 respondents of SMEs culinary  registered in  Ciganjur, South  Jakarta. The tool  used to analyze the data in this research is Partial Least Square (PLS) 3.0. The results obtained: (1) market orientation significantly influence the SMEs  culinary’s marketing performance; (2) entrepreneurial orientation does not influence  the SMEs culinary’s marketing performance.